Success story of rehabilitation - Gadgil, Medha (Mumbai RRD GOI, 2018)
This book highlights untiring efforts of Government of Maharashtra in rehabilitation of Project Affected Persons (PAPs). As per Narmada Water Dispute Tribunal Award, the share of Maharashtra is 10.914 TMC water and 391.50 MW (27%) Hydroelectricity from the project. This book illustrates the problems faced by the officials while implementing the rehabilitation of this project and how this project was completed by overcoming those problems during the last 57 years. It also highlights how all the rehabilitation issues in this inter-state project have been resolved amicably. This project will serve as a pilot project for guidance of the rehabilitation sector.
Sardar Sarovar (Narmada) project
Keywords: IAS as an Author; Rehabilitation; Sardar Sarovar Project